Addressing the Training Gap for Ammonia-Fuelled Propulsion Systems: A Literature Review and Proposal for a New Job Training Program (Asean Journal of Engineering Education, 2023)
The maritime industry is increasingly turning to ammonia as a promising alternative marine fuel to achieve sustainable and environmentally friendly shipping practices. However, this transition presents operational challenges and safety concerns that necessitate specialized training for marine engineers. This literature review examines the existing research on ammonia's operational challenges and identifies a critical research gap - the lack of comprehensive training programs for marine engineers to handle ammonia-fuelled propulsion systems effectively. The review highlights the importance of theoretical knowledge and practical training in such programs to ensure safe and efficient operations. Additionally, the study analyzes current training initiatives provided by leading maritime education institutions, Det Norske Veritas (DNV) Energy Academy, Lloyd's Maritime Academy, and Maritime Training Academy, to derive insights for developing a new job training program on ammonia-fuelled propulsion ships. The proposed program encompasses theoretical lectures and practical hands-on experiences, empowering marine engineers to navigate ammonia as a fuel source proficiently. By addressing this research gap and providing specialized training, the maritime industry can facilitate a smooth transition to ammonia as a marine fuel, promoting reduced environmental impacts and enhanced operational efficiency in the shipping sector. This literature review and proposal aim to contribute to the ongoing efforts in achieving sustainable and responsible maritime practices in the context of ammonia as a promising alternative marine fuel.
Keywords: Ammonia propulsion; Marine engineering; Sustainable maritime practices; effective training initiatives; Environmental sustainability; Operational complexities.